Wave mechanics for ocean engineering - Boccotti, P. (Paolo) (Elsevier oceanography series ;, 2000)
In a unitary way, this monograph deals with a wide range of subjects related to the mechanics of sea waves. The book highlights recent theoretical results on the dynamics of random wind-generated waves, on long-term wave statistics, and on beach planform evolution. A fresh approach is given to more traditional concepts. For example, new evidence from a recent series of small-scale field experiments is used to introduce some crucial topics like wave forces. Also, the book gives some worked examples for the design of offshore or coastal structures. An exciting subject dealt with in the book is the quasi-deterministic mechanics of three-dimensional wave groups in sea storms, and the loads exerted by these wave groups on offshore structures. The text is intended for researchers and graduate students in ocean engineering, but may also be understood by undergraduates. The more complex concepts are explained with examples or more extensive case studies.